Recombination between vaccine and field strains of canine parvovirus is revealed by isolation of virus in canine and feline cell cultures - Mochizuki, M.(Kyoritsu Seiyaku Corp., Tokyo (Japan)); Ohshima, T; Une, Y; Yachi, A (Journal of Veterinary Medical Science, 2008)
Canine parvovirus type 2 (CPV) is a pathogen that causes severe hemorrhagic gastroenteritis with a high fatality rate in pups worldwide. Since CPV emerged in the late 1970s, its origin has been explored with the conclusion that CPV originated from feline panleukopenia virus or a closely related virus. Both high mutation rate and recombination are assumed to be key factors in the evolution of parvoviruses. Here we provide evidence for natural recombination in CPV isolated from dogs in cell culture. Antigenic and genetic properties of isolates from 10 diseased pups were elucidated. Six pups had been vaccinated beforehand with live combined vaccine containing original antigenic type CPV (CPV-2). Six isolates recovered from 4 vaccinated pups in cell cultures were found to contain either CPV-2 or CPV-2-like viruses. The other isolates, including all those from non-vaccinated pups, were CPV-2b viruses. Antigenic typing of two CPV-2-like isolates, 03-029/M and 1887/f, with a monoclonal antibody panel suggested they were a mixture of CPV-2 and CPV-2a (03-029/M) and a recombinant of CPV-2 and CPV-2b (1887/f). Genetic analysis of the VP1 gene indicated that isolate 03-29/M was a mixture of CPV-2, CPV-2a and a recombinant of CPV-2 and CPV-2a viruses, while isolate 1887/f was composed of a recombinant of CPV-2 and CPV-2b viruses. This is the first demonstration of natural CPV recombination in the field and suggests that recombination in the evolution of CPV is a more frequent and important process than previously believed.